2006
DOI: 10.2165/00002512-200623030-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Controlled Clinical Trial Evaluating Changes in Therapeutic Efficacy and Oxidative Parameters after Treatment with Propionyl L-Carnitine in Patients with Peripheral Arterial Disease Requiring Haemodialysis

Abstract: Intravenous administration of propionyl L-carnitine to haemodialysis patients with PAD improves both haemodynamic flow and the oxidative profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Previous studies have shown that oxidative stress is associated with PAD in hemodialysis patients. Reducing oxidative stress in these patients with propionyl L-carnitine can significantly increase nitric oxide formation, decrease vasoconstrictive endothelin-1 production, and improve vascular hemodynamic flow 46, 47 . Together, these findings suggest that the association between L5% and lower-extremity PAD in uremia patients may in part be attributed to the promotion of oxidative stress by L5 LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oxidative stress is associated with PAD in hemodialysis patients. Reducing oxidative stress in these patients with propionyl L-carnitine can significantly increase nitric oxide formation, decrease vasoconstrictive endothelin-1 production, and improve vascular hemodynamic flow 46, 47 . Together, these findings suggest that the association between L5% and lower-extremity PAD in uremia patients may in part be attributed to the promotion of oxidative stress by L5 LDL.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PLC has shown therapeutic benefits in the management of disease such as peripheral vascular disease, myocardial ischemia, congestive heart failure, and erectile dysfunction ( Table 2) [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Clinical Indication Of Propionyl-l-carnitinementioning
confidence: 99%
“…A significant increase in ABI was observed in several studies [54,55,[59][60][61]65], but other studies produced no differences or reductions. In addition, some of these studies also observed a reduced peripheral resistance measured by Continuous Wave Doppler of the lower limbs [61,65].…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…The activity of propionyl L-carnitine on oxidative profile has been evaluated in two studies in patients with chronic renal insufficiency [54] or PAD associated with type 2 diabetes [59]. These studies showed positive effects on plasma markers of oxidation [malondialdehyde (MDA), 4-hydroxynonenal (4-HNE) and the nitrite/nitrate (NO 2 /NO 3 ) ratio] after 12 months treatment.…”
Section: Oxidative Profile and Endothelial Functionmentioning
confidence: 99%